Reducing Water Losses in Potable Water Distribution Systems: A Case Study of Kocaeli - Burak Kızılöz (Doğal Afetler ve Çevre Dergisi)
Water utilities with limited water resources have difficulties arising from high levels of water losses in water supply networks. However, reducing these losses can be possible by monitoring, checking and managing the network correctly. In this study, it is aimed to reduce high levels of water losses through the hydraulic model by digitizing the existing drinking water assets in the central district of Kocaeli, İzmit. In parallel with this purpose, 69 district metered area have been established firstly within 567.95 km of İzmit with a total network length of 1143 km. In each isolated area, 684 of 2116 suspected leakages have been repaired by using active leakage control methods. Secondly, the pressure management system has been applied by using pressure breaker valves to prevent undetected leakages. A reduction of approximately 192.48 l/s has been achieved in the minimum night flow after active leakage control methods and pressure management activities. Thirdly, the replacement of end-of-life water meters has contributed to reduce apparent losses in isolated area. In conclusion, the water loss which was 45.40% in 2014 could be reduced to 29.50 % in İzmit district in 2019. According to the active leakage control, pressure management and meter replacement methods applied in this study, reducing water loss to 25 % throughout Kocaeli is possible by using these methods in other districts.